Assessing episodes in verbalization process of EFL students’ collaborative writing - Ani Susanti; Utami Widiati; Bambang Yudi Cahyono; Tengku Intan Suzila Tengku Sharif (Universitas Syiah Kuala, 2022)
One of the ways to engage EFL students in writing is to assign them to work collaboratively. Collaborative writing requires a verbalization process resulting in episodes related to language, texts, and scaffolds. This study examined the use of episodes in collaborative writing of EFL students set in pairs by the teacher. It identified the most productive type of episodes which include language-related episodes (LREs), text-related episodes (TREs), and scaffolding episodes (SEs). It also scrutinized the categories of episodes within each type of episode. The study involved 20 pairs of Indonesian students from the English Department of a reputable university in Yogyakarta, Indonesia. The students were given an integrated reading-writing task and asked to work in pairs. The results of the study showed that SEs were the most productive type of episode, followed by LREs in the moderate occurrence, and TREs, which were the least productive type of episode. The results also revealed that among the categories in each type of episode, lexis-focused (LREs), organization-focused (TREs), and repetition (SEs) were more productive than the other categories of episodes. These results imply that the most productive categories of episodes could be catalysts in the teaching of writing, which employs collaborative writing tasks either in pairs or in small groups. This study offers insights into creating activities to encourage writing activities that especially involve types of pairings.